Effects of Bacille Calmette Guerin (BCG) vaccination during COVID-19 infection. (November 2021) - Chowdhury, Utpala Nanda; Faruqe, Md Omar; Mehedy, Md; Ahmad, Shamim; Islam, M. Babul; Shoombuatong, Watshara; Azad, A.K.M.; Moni, Mohammad Ali
Abstract: The coronavirus disease 2019 (COVID-19) is caused by the infection of highly contagious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also known as the novel coronavirus. In most countries, the containment of this virus spread is not controlled, which is driving the pandemic towards a more difficult phase. In this study, we investigated the impact of the Bacille Calmette Guerin (BCG) vaccination on the severity and mortality of COVID‐19 by performing transcriptomic analyses of SARS-CoV-2 infected and BCG vaccinated samples in peripheral blood mononuclear cells (PBMC). A set of common differentially expressed genes (DEGs) were identified and seeded into their functional enrichment analyses via Gene Ontology (GO)-based functional terms and pre-annotated molecular pathways databases, and their Protein-Protein Interaction (PPI) network analysis. We further analysed the regulatory elements, possible comorbidities and putative drug candidates for COVID-19 patients who have not been BCG-vaccinated. Differential expression analyses of both BCG-vaccinated and COVID-19 infected samples identified 62 shared DEGs indicating their discordant expression pattern in their respected conditions compared to control. Next, PPI analysis of those DEGs revealed 10 hub genes, namely ITGB2, CXCL8, CXCL1, CCR2, IFNG, CCL4, PTGS2, ADORA3, TLR5 and CD33. Functional enrichment analyses found significantly enriched pathways/GO terms including cytokine activities, lysosome, IL-17 signalling pathway, TNF-signalling pathways. Moreover, a set of identified TFs, miRNAs and potential drug molecules were further investigated to assess their biological involvements in COVID-19 and their therapeutic possibilities. Findings showed significant genetic interactions between BCG vaccination and SARS-CoV-2 infection, suggesting an interesting prospect of the BCG vaccine in relation to the COVID-19 pandemic. We hope it may potentially trigger further research on this critical phenomenon to combat COVID-19 spread. Highlights: Primary focus of this study lies on exploring genetic link of BCG vaccination to the severity and mortality of COVID-19 patients. Transcriptomic analysis resulted the contributory genes with discordant expression patterns in SARS-CoV-2 infections and BCG vaccination. Gene ontology and signalling pathway sharing assisted better molecular insight about the impact of the BCG vaccination on COVID-19. Hub proteins obtained in protein-protein interaction network could accelerate the therapeutic development to fight against COVID-19. Identified TFs and miRNAs can be treated as candidate biomarkers while protein-drug interaction may reveal potential drug targets for COVID-19.